The Debt-Growth Nexus in Nigeria: An Empirical Evidence - Adekunle, Ahmed Oluwatobi (International Journal of Economics and Financial Issues, 2022)
This study examines debt-growth nexus in developing countries, Nigeria, using annual data from 1986-2020. The data were sourced from CBN Statistical bulletin and WDI, ARDL techniques were employed to analyse the data. The findings of the study showed that domestic debt outstanding is negative related to growth in the long run though it is growth enhancing in short-run. External debt is negative related to advancement in long run while in short run is positive related. In the long run education is positive connected to growth but negative related to growth in the short run. The findings suggested that the national authority should channel both external and domestic debt to the education and infrastructural expansion which can lunch the economy to be more productive and diversified.